PENGEMBANGAN MODUL BERKARAKTER PADA MATERI SISTEM PERNAFASAN UNTUK SMA - Mawita, Fera; Sudirman, Sudirman; Fifendy, Mades (STKIP PGRI Sumbar, 2013)
ABSTRACT There is no teacher makes character modules on subjects of biology. The use of a limited number of books and supporting students who came from the printing module used student does not meet the actual module components. There are also weaknesses in the present picture of them colorless, the concepts of the material in less clear learning objectives, in addition to supporting books and modules that are used do not seem character values. As a result students difficulty doing exercises or questions that the teacher and students are not stimulated to develop character values both at school and in public life. To the researchers have developed teaching materials in the form of character modules. This research aims to produce valid character module practical matter respiratory system. This type of research is the development of research (research and development) with 4-D models that define (definition) consists of the analysis of the curriculum, desaign (design) module and enter the value of character, develop (development) and dessiminate (spread). This research has been carried out and campus STKIP PGRI and SMAN 6 Padang, from the month of March-April 2013. At this stage of develop test the validity (2 teachers and 2 professors) and the practicalities by two biology teachers and students of class XI IPA4 many as 33 people. Character module on material generated respiratory system is very valid criteria for high school and very practical, with an average of 87.08 % validation (very valid) and the average value of the practicalities of 93.58 % (very practical). Expected products resulting from the research is the development of character modules can be used by teachers in the learning process, especially in SMA N 6 Padang, the teacher should remind students to practice honesty in filling out worksheets and do not see the answer key sheet module before work is completed.